RESISTANCE STATUS OF BLOWFLY, CHRYSOMYA MEGACEPHALA AGAINST SELECTED INSECTICIDES FROM CENTRAL PUNJAB, PAKISTAN - Samiya Javaid; Muhammad Khalid Mukhtar; Naila Amjad; Shafaat Yar Khan; Hafiz Azhar Ali Khan (Journal of Animal and Plant Sciences, 2025)
The role of Chrysomya megacephala in transmitting various pathogens highlights the urgent need to control this species to ensure public health safety. In the present study resistance status of blowfly populations was determined against five insecticides (deltamethrin, fipronil, chlorpyrifos, imidacloprid and pyriproxyfen). Blowfly populations were collected from different localities of Central Punjab, Pakistan i.e Sargodha, Bhalwal, Faisalabad and Chiniot. The adult flies of F1 generation were used for residual bioassay against five concentrations of each insecticide. Moderate level of resistance at LC50 ranged from 8.57-15.84 folds was found against deltamethrin, 4.84-8.38 folds for fipronil, and 3.51-6.65 folds for chlorpyrifos. The RR values at LC50 for imidacloprid and pyriproxyfen ranged from 3.98-5.63 folds and 3.34-4.66 folds, respectively. Faisalabad population of blowflies revealed very low resistance ratios against all tested insecticides whereas Bhalwal population of blowflies showed highest RR values as compared to populations of other locations. The present study showed varying level of resistance in blowfly populations from area to area and insecticide to insecticide. Therefore, for the control of resistance development in blowflies in near future to mitigate the risks associated with insecticide use, it is essential to establish a proper control mechanism, incorporating techniques like mosaic, rotational, and periodic application strategies.
Keywords: Chrysomya megacephala; Insecticides; Resistance; Toxicity; Lethal concentration